TEACHING READING COMPREHENSION ON DESCRIPTIVE TEXT BY USING RECIPROCAL METHOD - Redi Muhlis; Hendra Husnussalam (IKIP Siliwangi, 2022)
This research began with students who had problems in understanding descriptive reading material. Overcoming students' difficulties in understanding descriptive reading by applying the reciprocal teacing method. The objectives of this research were 1) to determine the scenario and implementation of learning descriptive text for reading comprehension using reciprocal methods, 2). To find out the responses of teachers and students on learning comprehension of reading descriptive texts using reciprocal methods, 3). Identifying student difficulties in learning Reading Comprehension using the reciprocal method. This research uses a qualitative method, the instruments used in this study are observation, questionnaires, interviews. The research results obtained that: 1) the planning and application of reciprocal methods on descriptive text material run well to provoke student to become an active on learning process. 2) the teacher's gave a good response to the scenario and implementation on learning reading descriptive text using reciprocal techniques. 3) the students have difficulty on finding vocabulary in descriptive text. Keywords: Reading Comprehension, Descriptive Text, Reciprocal Method